Εκδήλωση πυρκαγιάς σε Ε/Γ-Ο/Γ πλοίο στην Ερεικούσα (HellenicCoastguard, 2022)
: Καλησπέρα! Συνεχίζοντας με το πρόγραμμα του ΕΚΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟΝΤΟ